Community-Based Livestock Entrepreneurship Assistance to Strengthen Local Economic Self-Reliance at the Urban Village Level - Henry Dunan Pardede; Arwin Tannuary; Heru Sugara; Hengki Mangiring Parulian Simarmata; Demak Claudia Yosephine Simanjuntak; Purnama Yanti Purba; Jusra Tampubolon (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
This community service program focused on community-based livestock entrepreneurship assistance aimed at strengthening local economic self-reliance in Pondok Sayur Subdistrict, Pematangsiantar City. The activity was conducted in the form of a workshop and attended by 30 community members, primarily farmers and livestock breeders. The main speaker, Henry Dunan Pardede, S.P., M.M., delivered practical insights on strategies for developing farmer groups, with particular emphasis on financial management and marketing strategies for livestock-based enterprises. The program highlighted the importance of simple bookkeeping practices and effective marketing planning as key foundations for sustainable farmer group development. The implementation of the activity was supported through collaboration among Universitas Murni Teguh PSDKU Pematangsiantar, Politeknik Bisnis Indonesia, Universitas Prima Indonesia, the Head of Pondok Sayur Subdistrict, and the Pematangsiantar City Land Office. Evaluation results indicated that approximately 90% of participants expressed satisfaction with the program, reflecting high relevance and practical applicability of the materials delivered. Overall, the workshop effectively enhanced participants’ awareness, knowledge, and readiness to manage livestock enterprises more professionally, while reinforcing the strategic role of higher education institutions in community empowerment and local economic development.